VD_FINDINFO Jug / 2025 / 144 vom 1. Januar 2021 - VD Tribunal cantonal (2021)
FIXATION DE LA PEINE, CONSTATATION DES FAITS, TORT MORAL, VIOLENCE DOMESTIQUE | 123 ch. 1 al. 1 CP, 123 ch. 2 al. 5 CP, 180 al. 1 CP, 180 al. 2 let. b CP, 181 CP, 22 ad 181 CP, 47 CP, 10 CPP (CH), 123 CPP (CH)